Large deformation evolution and failure mechanism analysis of the multi-freeface surrounding rock mass in the Baihetan underground powerhouse - Wang, Meng; Li, Hai-bo; Han, Jin-qi; Xiao, Xin-hong; Zhou, Jia-wen (Engineering failure analysis, 2019)
In a large underground powerhouse, the surrounding rock mass at the intersection of the caverns has multiple free faces. This rock mass is more susceptible to stability issues because of its peculiar structure. This paper takes the Baihetan underground powerhouse as a case study example, wherein the failure issue of multi-freeface surrounding rock mass appears prominent. Through analysis of monitoring data from multi-point extensometers, it has been concluded that the average daily deformation of the main powerhouse sidewall on downstream side in the presence of multi-freeface rock mass proves larger than that on upstream side; the maximum deformation reaches 0.48 mm/d, overshadowing that at the rock anchor beam as well. The multi-freeface surrounding rock mass is not only more subject to large deformation but also shows more sensitivity to positional change in the working face. Moreover, the sidewall and rock anchor beam witness greater spatial deformation compared with the arch area from a spatial perspective, and from the point of time the time-related deformation presents a step growth, which tends to eventually converge. The failure mechanism is also discussed, where fiercer stress redistribution and denser cracks account for the greater deformation of the multi-freeface surrounding rock mass. In general, a wide range of underground powerhouse stability issues has arisen with respect to huge-scale and adverse geological conditions since the construction of the Baihetan Hydropower Station, and settling these issues will undoubtedly have milestone significance with regard to the construction and development of hydropower engineering projects among the worldwide. •Spatial-temporal characteristics of deformation in powerhouse are studied.•Deformation at different location in powerhouse is analyzed contrastively.•Large deformation evolution of multi-freeface surrounding rock mass is discussed.•Failure mechanism of multi-freeface surrounding rock mass is presented.